(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2026)
The rapid growth of padel sports requires a tournament management system capable of managing competitions effectively, accurately, and in an integrated manner. Manual tournament management is still prone to score recording errors, ranking calculation mistakes, match scheduling conflicts, and errors in managing knockout brackets. This study aims to design and implement a web-based padel tournament management system capable of automating tournament management using Round Robin and Knockout formats. The research method used is the Incremental system development method, which is carried out gradually through requirements analysis, system design, implementation, testing, and system evaluation stages. System testing was conducted using the Black Box Testing method to ensure that all system functions operate according to user requirements. The results showed that the system successfully automated padel scoring validation, including two-game difference calculations and 7-6 tiebreak handling, while also managing match scheduling, Round Robin standings, and Knockout brackets automatically. The system was also able to handle seeding processes, bye allocation, and automatic winner advancement to the next round effectively. In conclusion, the developed web-based padel tournament management system successfully improved tournament management efficiency, minimized human error risks, and supported better tournament administrative integrity.